Success of Students Participated in Quit and Win Campaign in Elazığ Police Academy - Açık, Yasemin; Gülbayrak, Canan; Deveci, S. Erhan; Ozan, A. Tevfik (Fırat University, 2002)
Aim: This study was carried out to increase the rate of participation of Elazığ Police Academy Students to the campaign with award to quit smoking and to evaluate success rate of participated students after one month. Materials and Methods: Among total of 217 smokers, 98 students participated in the study. By consulting the witnesses and measuring CO levels in inhaled air, fidelty of decleration to be successful of quiting smoking of participated students were established. Results: Smoking rate of students, participation to the campaign and success rate were 63.4%, 45.1% and 14.3%, respectively. Mean age of participants was 25.9 ± 1.3 year. Average number of cigarettes smoked per day, smoking period and number of attemps to quit smoking were 15.7 ± 5.3 cigarette / day; 7.6 ± 2.7 year and 2.7 ± 3.1 times, respectively. The rate of success during campaign was 26.3% in 1-4 year smokers, 6.7% in 5-9 year smokers, 17.6% in 10+ year smokers before campaign. Success rate of participants who never intended quiting smoking was 0% where as it was 21.1% in smokers who tried to quit at least 5 times. Conclusion: Although participation to the campaign is high, rate of quiting smoking is low. Due to importance of quit and win campaigns in the actions against smoking, number of campaigns and support to be given the participant during campaign must be increased.

Amaç: Bu araştırma polis okulu öğrencilerinin ödüllü sigarayı bırakma kampanyasına katılma oranlarını artırmak ve kampanyaya katılan öğrencilerin 1 ay sonraki başarı oranlarını ölçmek amacıyla yapılmıştır. Gereç ve Yöntem: Öğrencilerin sigara içen 217'si araştırmanın evrenini, kampanyaya katılan 98 kişi ise örneklemini oluşturmuştur. Kampanyaya katılıp başarılı olduklarını söyleyen öğrencilerin, şahitlerine sorularak ve solunum havasındaki CO düzeyleri ölçülerek sigara içmedikleri doğrulanmıştır. Bulgular: Öğrencilerin sigara içme oranı %63.4, kampanyaya katılım oranı %45.1, başarı oranı %14.3'tür. Kampanyaya katılan öğrencilerin ortalama; yaşı 25.9 ± 1.3, günde içtikleri sigara sayısı 15.7 ± 5.3, sigara içtikleri süre 7.6 ± 2.7 yıl ve bırakmayı deneme sayısı 2.7 ± 3.1'dir. Kampanya dönemindeki başarı oranı; kampanya öncesi 1-4 yıl sigara içenlerde %26.3, 5-9 yıl içenlerde %6.7 ve 10+ yıl içenlerde %17.6'dır. Kampanya öncesi dönemde sigarayı bırakmayı hiç denemeyenlerin kampanyadaki başarı oranı %0 iken, 5+ kez deneyenlerin %21.1'dir. Sonuç: Öğrencilerin kampanyaya katılım oranları yüksek, sigara bırakma oranları ise düşüktür. Bırak Kazan kampanyalarının, sigara ile mücadeledeki öneminden dolayı kampanya sayısı ve katılımcılara kampanya süresince verilecek destek artırılmalıdır.
Elazığ Polis Okulu'nda Düzenlenen Sigarayı Bırak Kazan Kampanyasına Katılan Öğrencilerin Başarı Durumları